Pro-active positioning of a social robot intervening upon behavioral disturbances of persons with dementia in a smart nursing home. (October 2019) - Nauta, Johannes; Mahieu, Christof; Michiels, Christophe; Ongenae, Femke; De Backere, Femke; De Turck, Filip; Khaluf, Yara; Simoens, Pieter
Abstract: Behavioral disturbances of persons with dementia residing in a nursing home impose a significant burden on other residents and on the care staff. A social robot can provide an adequate technological support tool for the caregivers by approaching a resident that exhibits a behavioral disturbance. In this paper, we focus on how to position the robot in the nursing home, taking into account the profile and location of the residents. We minimize the time between the detection of a behavioral disturbance and the robot having arrived near the resident and starting an interaction scenario. Our algorithm is evaluated using realistic data that was collected during 3 months in two Belgian nursing homes.